Integrating Good Governance, Integrity Zone, and Digitalization: A Synergistic Model for Immigration Service Reform in Indonesia - Astuti, Rita Kusuma; Wirdhiningsih, Virra; Pujonggo, Seno Setyo; Jannah, Rahmawati Nurul; Maulidia, Hanifa; Priyatno, Mas Budi; Febrianto, Arief (Universitas Padjadjaran, 2026)
Public service reform in sensitive sectors like immigration requires a balance between sovereignty control and service excellence. This study aims to develop an effective reform model by synthesizing three strategic pillars: Good Governance (GG), the Integrity Zone (IZ) program, and Digitalization. Utilizing a qualitative policy synthesis and thematic analysis of institutional data (LKjIP 2024) and longitudinal records (2018-2024), the research evaluates the implementation trajectory of 103 immigration units in Indonesia. The findings reveal a